VizieR Online Data Catalog: Gaia-ESO Survey. Trumpler 23 (Overbeek+, 2017) - Overbeek, J. C.; Friel, E. D.; Donati, P.; Smiljanic, R.; Jacobson, H. R.; Hatzidimitriou, D.; Held, E. V.; Magrini, L.; Bragaglia, A.; Randich, S.; Vallenari, A.; Cantat-Gaudin, T.; et al. (2017)
Data for GES are taken with the Fiber Large Array Multi-Element Spectrograph (FLAMES) on the VLT at the European Southern Observatory. FLAMES has two instruments, the medium-resolution multi-object spectrograph GIRAFFE and the high-resolution Ultraviolet and Visual Echelle Spectrograph (UVES). For intermediate-age OCs with prominent red clumps, GES targets are selected as follows: likely clump stars are observed with UVES, so that the most time-intensive targets are most likely to be members, followed by probable red giants if the clump is sparse. Main sequence stars down to V=19 are observed with GIRAFFE, using the HR9B setup primarily for stars of spectral type A to F and the HR15N setup for cooler stars. General GES target selection methods are outlined in Bragaglia et al. (in prep.). (6 data files).
Keywords: Abundances; Clusters: open; Effective temperatures; Radial velocities